Can a rhythmic intervention support reading development in poor readers?. (September 2019) - Hallam, Susan
There is increasing interest in the wider benefits of music in relation to reading, although relatively little evidence relating to the role that music might play in developing literacy skills in those experiencing difficulties. The research reported here explores the impact of a rhythmic intervention involving clapping, stamping, and chanting to music while following notation on a chart. The intervention took place for 10 minutes each week over a 10-week period with groups of 10 children, who had lower than average reading scores. The children were in the first year of secondary school (11–12 years old). The NARA II test was selected to assess reading accuracy, comprehension, and reading rate before and after the intervention with alternative forms of the test being used. Pupils ( N = 354) attending six secondary schools in the UK participated and were randomly allocated to control (174) and intervention groups (180). Multivariate analysis of variance of change scores across the period of the intervention revealed statistically significant differences between control and intervention groups in reading accuracy ( p = .014) and comprehension ( p = .001) but not in reading rate. The differences in reading accuracy were equivalent to 1.38 standardized scores and reading comprehension, 2.33 standardized scores.